Canon, value and artistic culture: critical inquiry about the new processes of assigning value in the digital realm - Rodríguez-Ortega, Nuria (My University, 2014)
Se analiza los nuevos procesos de asignación de valor a los objetos de la cultura relacionados con el paradigma digital.
Keywords: Comunicación y cultura; Canon; Digital humanities; Digital art history; Social production of knowledge; Critical thinking